PENGEMBANGAN LITERASI, NUMERASI, ADAPTASI, TEKNOLOGI, OLEH KAMPUS MENGAJAR ANGKATAN III DI SMP SWASTA HARAPAN BUNUT - Maria Rahayu Gurning (Abdi Implementasi Pancasila:Jurnal Pengabdian kepada Masyarakat, 2022)
The Independent Learning Campus Independent Program (MBKM) is one of the programs organized by the Ministry of Education and Culture. The Campus Teaching Program is one of the programs in the Merdeka Learning Campus Merdeka Program which aims to teach, assist technology, and assist school administration and teachers. One of the schools targeted for the Teaching Campus program is the Harapan Bunut Private Junior High School which is located in West Bunut, West Kisaran sub-district, Kisaran District, Asahan Regency.The purpose of student participation in the Teaching Campus program is a process of adding relationships, adding experiences outside the world of lectures, developing students' insight, character and soft skills, encouraging and spurring national development by fostering student motivation to participate in development, as well as increasing the role and the real contribution of universities and students in the development of education in Indonesia. The results of this study, students’ motivation tu read increases, and becomes more confident to appear in front of the class. And the level of students’ understanding of numeracy is better than before, both in multiplication, addition, and division. This is in accordance with the achievements containend in the objectives of the Teaching Campus Program.